2016
DOI: 10.1038/am.2016.132
|View full text |Cite
|
Sign up to set email alerts
|

In situ anchoring of Co9S8 nanoparticles on N and S co-doped porous carbon tube as bifunctional oxygen electrocatalysts

Abstract: The development of cost-effective yet highly active and robust bifunctional electrocatalyst for oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) has been at the forefront of research into regenerative fuel cells and metal-air batteries. Here we report Co 9 S 8 nanoparticles grown in situ on nitrogen-and sulfur-doped porous carbon (Co 9 S 8 /NSPC) as a bifunctional catalyst for OER and ORR using poly(2-aminothiazole) as a novel all-in-one multifunctional precursor. Unexpectedly, Co 9 S 8 /NSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
89
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(97 citation statements)
references
References 45 publications
(55 reference statements)
7
89
0
1
Order By: Relevance
“…The peaks at 161.5 and 162.3 eV are attributed to the S 2p 3/2 and S 2p 1/2 of CoS, respectively, basically arising from Co 9 S 8 . While the peaks at 163.5 and 165.1 eV are attributed to CSC, and the peak at 167.9 eV can be assigned to SO 4 2− . The presence of CSC conforms that S atoms were well doped into carbon matrix besides forming the Co 9 S 8 nanoparticles.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…The peaks at 161.5 and 162.3 eV are attributed to the S 2p 3/2 and S 2p 1/2 of CoS, respectively, basically arising from Co 9 S 8 . While the peaks at 163.5 and 165.1 eV are attributed to CSC, and the peak at 167.9 eV can be assigned to SO 4 2− . The presence of CSC conforms that S atoms were well doped into carbon matrix besides forming the Co 9 S 8 nanoparticles.…”
Section: Resultsmentioning
confidence: 78%
“…It is found that Co 9 S 8 /NSCNFs‐850 exhibits superior OER activity with the lowest overpotential of 302 mV to afford 10 mA cm −2 , which is smaller than those of Co 9 S 8 /NSCNFs‐950 (314 mV) and Co 9 S 8 /NSCNFs‐750 (333 mV), and even 30 mV smaller than that of commercial RuO 2 catalyst. Notably, this overpotential is smaller than those of most reported cobalt sulfide‐based OER catalysts, such as Co 9 S 8 /NSPC9‐45 (310 mV), Co@Co 9 S 8 ‐180 (350 mV), and CoS 2 (400)/N, S‐GO (380 mV), and more advantageous compared with highly active non‐noble‐metal OER catalysts (Table S1, Supporting Information). Additionally, Co 9 S 8 /NSCNFs‐850 also reveals a lower onset potential of 1.48 V versus RHE, further indicating the excellent OER activity.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…water, dinitrogen, inactivated metal oxide) into high-value products (e.g. hydrogen, ammonia, activated cations and anions) [3,4]. Thus, electrocatalysis, in the broadest sense, dominates the electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%